The Effectiveness Of Using Intens Book (Interactive English Book) Media In Learning English - Anandita, Septian Ragil; Muasyifah, Qonny; Afidah, Nurul; Agustina, Ulfa Wulan (EDUSCOPE: Jurnal Pendidikan, Pembelajaran, dan Teknologi, 2024)
ABSTRACT This research is generally attempted to find the effectiveness of using INTENS BOOK (Interactive English Book) media in learning English for the class X-AKL-3 students at SMK PGRI 1 Jombang academic year 2022/2023. To know whether this media is effective or not, the researcher used pre-experimental research applied in X-AKL-3 class. The research had been done in six meetings that were designed: first meeting was for pre- test, 4 meetings were for treatments, and the last meeting was for post-test. As the quantitative method, the researcher analyzed the data by using the paired sample t-test. The result showed that there was siginificant difference on the student’s mean score of pre-test’s score was 66,12. Then in post-test, the mean score was 84,12. In other words, INTENS BOOK media is effective in learning English for advance learner, especially for first grade of senior high school students. Key words: Intens Book Media, Learning English ABSTRAK Penelitian ini secara umum bertujuan untuk mengetahui keefektivan penggunaan media INTENS BOOK (Interactive English Book) dalam pembelajaran bahasa Inggris siswa kelas X-AKL-3 di SMK PGRI 1 Jombang tahun pelajaran 2022/2023. Untuk mengetahui efektif atau tidaknya media ini, peneliti menggunakan penelitian pra- eksperimental yang diterapkan di kelas X-AKL-3. Penelitian ini dilaksanakan dalam enam pertemuan yang dirancang pertemuan pertama untuk pre-test, empat pertemuan untuk treatment, dan pertemuan terakhir untuk post-test. Sebagai metode kuantitatif, peneliti menganalisis data dengan menggunakan uji-t sampel berpasangan . hasil penelitian menunjukkan bahwa terdapat perbedaan yang signifikan pada nilai rata-rata siswa terhadap nilai pre-test sebesar 66,12. Kemudian pada post-test diperoleh nilai rata-rata sebesar 84,12 . Dengan kata lain, media INTENS BOOK efektif dalam pembelajaran bahasa Inggris bagi siswa tingkat lanjut, khususnya untuk siswa kelas satu sekolah menengah atas. Kata kunci: Media Intens Book, Pembelajaran Bahasa Inggris